Institutions and Poverty: A Critical Comment Based on Evolving Currents and Debates - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2014)
Tebaldi & Mohan (2010, JDS) have established an empirical nexus between institutions and monetary poverty. We first, reflect their findings in light of recent development models, debates and currents in post-2010 literature. We then re-examine their results with a non-monetary and multidimensional poverty indicator first published in 2010. Our findings confirm the negative relationship and the nexus disappears with control for average income. Hence, confirming the conclusions of the underlying study that institutions could have an indirect effect on multidimensional poverty. In other words, the poverty eradication effect of institutions is through income-average as opposed to income-inequality. We discuss the confirmed findings in light of implications to: (1) debates over preferences in economic rights; (2) China's development/outlook; (3) the Chinese model versus sustainable development; (4) the Fosu conjectures; (5) Piketty's & Kuznets' celebrated literatures and (6) future research to ascertain the inequality mechanism.
Keywords: O11; P14; P16; I32; O17; O43; 330; poverty; institutions